Integration of Nahwu and Theology in the Book Risālah al-Maimūniyyah fī Tawḥīd al-Ājurrūmiyyah: A Literature Study - Bakiruddin, M; Munir, Moh. Sirojul (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2025)
This study is motivated by the limited research exploring the relationship between nahwu (Arabic grammar) and theology, particularly within classical works that systematically integrate both fields. Risālah al-Maimūniyyah fī Tawḥīd al-Ajurrūmiyyah by al-Idrīsī presents a unique approach by interpreting the text of al-Ajurrūmiyyah- a foundational treatise in Arabic semantics -through the lens of ‘ilm al-kalām. This phenomenon highlights an academic gap that has not been widely addressed in either linguistic or theological studies. The aim of this research is to analyze in depth the content of the work, specifically how grammatical concepts are interwoven with theological discussions, such as the explanation of God’s attributes -nafsiyyah, salbiyyah, and ma‘ānī- which are linked to the structure of marfū‘āt al-asmā’. The method employed is library research, examining the primary source, Risālah al-Maimūniyyah, which serves as a commentary on al-Ajurrūmiyyah, along with secondary literature relevant to both grammar and theology. The findings indicate that nahwu can be understood not only through a purely linguistic approach but also enriched through theological perspectives without contradicting conventional grammatical principles. The “theological grammar” approach presented in this work functions as an epistemic expansion that offers a new interpretive framework for reading al-Ajurrūmiyyah. This study contributes to opening a scholarly dialogue between Arabic linguistics and theology, while providing a foundation for further interdisciplinary development within Islamic studies.